Upravljanje avtorskih pravic na filmski glasbi - Damjan, Matija (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2022)
Music is an important expressive element in the film art. Slovenian legislation recognises a composer who creates music specifically for the use in a film (film score) as a co-author of the audiovisual work. Other authors of music used in audiovisual works are treated solely as musical authors. However, the creative work of film music composers differs from the contributions of other audiovisual artists as film music is created separately from other contributions and can easily be exploited independently, outside the scope of the audiovisual work. The fact that film music composers are simultaneously musicians and filmmakers is reflected in the Slovenian system of collective management of copyrights, which depends on whether film music is used in the context of an audiovisual work or as an independent musical work. This distinction partially deviates from the prevailing practice in other comparable legal orders. The paper analyses the concept of authorship of an audiovisual work and contributions to it under Slovenian law. It presents how the Slovenian system of collective management of copyrights in film music was shaped by the decisions of the Intellectual Property Office of the Republic of Slovenia, the Copyright Council and judicial practice. Controversial issues of legal regulation are defined and different interpretations represented by different stakeholders are presented.
Keywords: avtorske pravice; avtorsko pravo; filmska glasba; filmska umetnost; glasba; kolektivno upravljanje; skladatelji